2019
DOI: 10.3389/fneur.2019.01133
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Reduces Neuronal Apoptosis and Improves Blood-Brain Barrier Integrity After Traumatic Brain Injury

Abstract: Objective: To investigate whether methylene blue (MB) treatment can reverse neuronal mitochondrial dysfunction caused by oxygen glucose deprivation/reoxygenation (OGD) injury and then investigate whether MB treatment can reduce neuronal apoptosis and improve blood-brain barrier (BBB) integrity in traumatic brain injury (TBI) animals.Methods: Reactive oxygen species (ROS), mitochondrial membrane potential (MMP), and adenosine triphosphate (ATP) were used to evaluate mitochondrial function. The terminal deoxynuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
0
24
1
Order By: Relevance
“…Most likely, this effect was achieved due to the unique properties of MB, which can act as an alternative electron carrier [52]. It has been repeatedly shown that MB improves memory in various experimental models [53][54][55][56][57]. At the same time, we showed that at a concentration of 50 mg/kg/day, MB did not significantly increase the cognitive parameters of mice.…”
Section: Plos Onementioning
confidence: 56%
“…Most likely, this effect was achieved due to the unique properties of MB, which can act as an alternative electron carrier [52]. It has been repeatedly shown that MB improves memory in various experimental models [53][54][55][56][57]. At the same time, we showed that at a concentration of 50 mg/kg/day, MB did not significantly increase the cognitive parameters of mice.…”
Section: Plos Onementioning
confidence: 56%
“…BBB is considered a therapeutic target for TBI (Abrahamson and Ikonomovic 2020 ; Jing et al 2020 ; Kempuraj et al 2017 ; Shen et al 2019 ; Thal and Neuhaus 2014 ). Endothelial cells are connected by many tight junction proteins that form BBB and regulate the rate of microvascular permeability in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Evens blue (EB) dye extravasation was used to evaluate BBB permeability, as previously described ( 40 ). Briefly, mice were injected with 100 ÎŒl of 4% EB, and then perfused with phosphate buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…The TUNEL staining procedure was then performed as previously described (40). TUNEL and immunofluorescence staining of neuronal nuclei (NeuN) were combined to evaluate neuronal apoptosis.…”
Section: Tunel Assaymentioning
confidence: 99%
See 1 more Smart Citation